Проблемні аспекти судової мистецтвознавчої експертизи - Карпінська, Н.; Karpinska, N. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті автором здійснена характеристика судової мистецтвознавчої експертизи, проаналізовано деякі негативні тенденції, що впливають на її ефективність. Встановлено, що основними завданнями психолого-мистецтвознавчої експертизи при дослідженні матеріалів зображень, фільмів порнографічного характеру є встановлення художньої, історичної та культурної цінності об'єкта дослідження, спрямованості і ступеня впливу творів мистецтва на свідомість або несвідому сферу особистості або населення в цілому. Обґрунтовано висновок про те, що заміщення об’єктів судової мистецтвознавчої експертизи, пов’язане з некоректним визначенням функцій суспільної свідомості, зумовлює помилкове визначення як предмета доказування так і ознак порнографічної продукції, а також впливає на об’єктивність результатів експертизи. The article highlights judicial characteristics of art expertise, analyzes some negative trends that affect its efficiency. The author claims that the main research goals of psychological and art examination/expertise of the artistic/image materials, films of a pornographic nature are the identification of the artistic, historical and cultural value of the object under study, the tendencies and the degree of influence of these works of art on the consciousness or the unconscious sphere of the individual or the population as a whole. The main tasks of the art expert during the judicial complex psychological and art examination are: to ascertain the presence or absence of the main signs of pornography, unambiguousness of the portrayed or depicted material and decide whether they contain the metaphorical or figurative meaning or other stylistic means of the artistic language or not; to identify operator's personal options as to the pornographic photo-or-cinema production, whether there is a dialogue individualization of the characters or its complete absence. On the other hand, an expertpsychologist must solve the problems concerning the nature and the degree of the psychological impact of the materials under examination on the potential consumer, the presence/availability or absence of propaganda of violence, cruelty, unconventional and distorted forms of sexual relationships.
Problematic Aspects of the Judicial Expertise of Artistic Works
Keywords: судова мистецтвознавча експертиза; експерти; матеріали еротичного та порнографічного змісту; judicial art expertise; experts; materials of erotic and pornographic content